The Influence of Transformational Tutor Style on Postgraduate Students’ Innovative Behavior: The Mediating Role of Creative Self-Efficacy - Yan Ma; Min Chen; Huifen Guo; Wenxiang Fan; Lijie Lai (International Journal of Digital Multimedia Broadcasting)
Postgraduates being as the backbone of the innovative talent team, the enhancement of postgraduates’ innovative behavior has become the focus of higher education reform in the new era. Postgraduate students’ innovative behaviors are influenced by multiple factors, and mentorship plays a crucial role in the cultivation of postgraduate students’ innovative behaviors. This study is based on social cognitive theory and empirical analysis from the perspective of individual postgraduate students and mentorship cultivation. Multisource data were obtained from a research team attending a teacher training college in southwest China, and a questionnaire survey was conducted on 362 postgraduate students based on an online approach. The empirical study was conducted using SPSS software and AMOS software combined with hierarchical regression analysis and structural analysis of covariance to examine the mechanism of the effect of transformational tutoring style on postgraduate students’ innovative behavior, using creative self-efficacy as a mediating variable. The results showed that the transformational tutoring style had a significant positive effect on the innovation behavior of postgraduate students, and the creative self-efficacy partially mediated the effect of the transformational tutoring style on the innovation behavior. According to the findings of the study, the creative self-efficacy of postgraduate students is enhanced through the collaboration of “multiple” subjects; the “integrated” cultivation model is built to create a transformative tutor team; a mentoring community is established. The study is aimed at providing a reference for the cultivation of innovation ability of master students.